KODE LINIER DARI GRAF STRONGLY REGULAR - Febrian Rahman, Adhitya
Adjacency matrix of undirected graphs can define generator matrix of binary linear codes. Parity check matrix of that codes is obtained from transposing it's generator matrix. It is shown that the class of all graphs with n vertices leads to code that meet Gilbert-Varshamov bound. Some interesting codes are obtainable from strongly regulars graphs, since such codes admit an efficient decoding algorithm. Another interesting codes are obtainable from incidence matrix of 2-design that constructed from specific strongly regular graph.